Evaluating Scientific and Forensic Evidence - Underwood, Richard H. (2000)
Professor Underwood offers a critique of the present state of scientific and forensic evidence. In the context of discussing four challenges to the field, the author arms the practitioner with strategies and tactics for making effective use of scientific and forensic testimony